So pretty! The neural correlates of self-other vs familiar-other attractiveness comparisons. (2nd January 2019) - Kedia, Gayannée; Mussweiler, Thomas; Adam, Ruth; Ischebeck, Anja; Ihssen, Niklas; Linden, David E. J.
ABSTRACT: Previous research has demonstrated that comparing two persons activates a frontoparietal network associated with numbers and nonsocial magnitudes. However, it is unclear whether this network is also recruited by comparisons involving the self. Self-reflection engages self-serving motivations (e.g., the maintenance of a positive self-image) and is associated with specific brain structures, such as the medial prefrontal cortex (MPFC), the anterior insula (AI) and the anterior cingulate cortex (ACC). Self-other comparisons may thus rely on distinct neural activity. To clarify this question, we used fMRI and asked female participants to compare their own attractiveness (or the attractiveness of a familiar woman) to pictures of unknown women. Participants were slower for comparisons with targets whose attractiveness was similar to their own (or their familiar other). Yet although this behavioral result resembles the distance effect reported for nonsocial magnitudes, at the brain level, it was linked to the activity of the AI, the ACC and the MPFC. The effect of distance in these regions was stronger for self-other than familiar-other comparisons. We interpret these results in relation to previous literature in social psychology and social neuroscience.